Pengujian Black Box pada Aplikasi Penjualan Berbasis Web Menggunakan Metode Equivalents Partitions (Studi Kasus: PT Arap Store) - Maulana, Arief; Kurniawan, Arief; Keumala, Wini; Sukma, Verdian Ramadika; Saifudin, Aries (Program Studi Teknik Informatika Universitas Pamulang, 2020)
In a software test, validation is a process of checking whether the software meets the specifications and intended purposes. Data validation process that has not been maximized can result in data that is stored in the database is not appropriate, including the login process that becomes an error. This can be detrimental to the owner and user in using this application. Therefore, it is necessary to improve the quality of validation more accurately, so that it can help the owner in the accuracy of the data. Applications that are designed in such a way must go through a testing phase to ensure the quality of the software itself. A good test case is if the test has the possibility of finding an error that is not revealed. Among the many ways of testing Black Box, in this study the Equivalence Partition testing method was chosen. This method tests solving or dividing the input domain from the program into data classes so that a test case can be obtained, which is considered quite relevant to test sales applications at PT Arap Store. Stages of research carried out begins by determining the functionality to be tested, designing test scenarios, determining the data to be tested, determining input can be numeric values, range values, related value collections or Boolean conditions in accordance with the database structure that has been created, conducting experiments testing, documenting research results, and drawing conclusions. Based on the results of tests that have been carried out, it gives a conclusion that this software can be used properly, after a repair has been made on the errors found. However, this test can be said to be imperfect, because it is only done by using several sample forms. From the results of this test it is expected that the application can be used according to user requirements.